Relationship between brain structure on magnetic resonance imaging and motor outcomes in children with cerebral palsy: A systematic review - Arnfield, E.; Guzzetta, A.; Boyd, Roslyn (2013)
Magnetic resonance imaging (MRI) is recommended in all children with cerebral palsy (CP) where the aetiology has not been established, and the major presenting problem in CP is reduced motor capacity. A systematic review of the literature was performed to investigate the relationship between brain structure on MRI and motor outcomes in children with CP. A total of 37 studies met inclusion criteria, and were analysed in terms of (a) population characteristics, (b) MRI data, (c) motor outcome data, and (d) the relationship between MRI data and motor outcomes. All studies used a qualitative system to classify brain lesions; however, few reported information about the location and extent of lesions. Valid and reliable classifications of motor abilities were not always used, and three studies did not link motor findings to MRI features. There was, however, a relationship between the type of brain lesion on MRI and two specific motor outcomes, namely gross motor functional classification (using GMFCS) and motor type. This relationship could aid in the prediction and optimisation of early interventions for children with CP. There is also need for a quantitative MRI classification measure which includes detailed information about the location and severity of lesions. © 2013 Elsevier Ltd.